The Prolapsed Intussusceptum in a 4-month-old Male: A Case Report - Parveen Kumar; Yogesh Kumar Sarin; Nitin Jain (Mazandaran University of Medical Sciences, 2021)
A case of intussusception may be missed on initial presentation, if the physician is not vigilant or if non-specific symptoms are present. It may progress to prolapse per anus, if not attended to. We reported a case of intussusception, i.e. missed on the initial presentation by a local practitioner and progressed to prolapse per anus and perforation peritonitis. The patient was managed well and experienced an uneventful course.